Acquisition of an Olfactory Associative Task Triggers a Regionalized Down-Regulation of Adult Born Neuron Cell Death - Sultan, Sébastien; Lefort, Julie; Sacquet, Joëlle; Mandairon, Nathalie; Didier, Anne (Frontiers in Neuroscience, 2011)
Associative olfactory learning increased survival of adult born granule interneurons in the olfactory bulb at regions which are specific to the learned odorant. However, the mechanism shaping this odor-specific distribution of newborn neurons and its temporal relationship with the learning process are unknown. In the present study, using Bromodeoxyuridine or activated caspase3 labeling, newborn and apoptotic cells respectively were mapped in the granule cell layer of the olfactory bulb, just before, during and at the end of odor conditioning or pseudo-conditioning in adult mice. Results indicate that before and during training, when the task is not yet acquired, conditioned and pseudo-conditioned animals displayed the same density of newborn neurons. However, at the end of the conditioning, when the animals mastered the task, the density of newborn cells remained elevated in conditioned animals while it decreased in pseudo-conditioned animals suggesting newborn cell death in that group. Indeed, using Activated Caspase3/BrdU co-labeling, we found that the proportion of newborn cells among dying cells was reduced in conditioned animals mastering the task compared to non expert conditioned or pseudo-conditioned animals. The overall level of cell death did not change across training and was similar in conditioned and pseudo-conditioned groups, indicating that BrdU-positive cells were spared to the detriment of non-labeled cells. In addition, a fine analysis of cell distribution showed an uneven distribution of apoptotic cells, with lower densities in the medial part of the GCL where the density of newborn cells is high in conditioned animals. We conclude that acquisition of the task triggered the rescue of newborn neurons by a targeted regulation of cell death.